Book Review - Marketing Research: A Practical Approach - Kumar, Manoj (Serbian Journal of Management, 2013)
Book: Marketing Research: A Practical ApproachAuthor: Bonita KolbPublisher: Sage PublicationsISBN:  978-1-4129-4796-1First Published:  2008Reviewer: Manoj Kumar, Asst Professor, Indus Business Academy, Greater Noida, India